Strategi Peningkatan Daya Saing Pengembangan Agribisnis Kopi Di Sumatera Barat - Rahmi Awalina; Ayendra Asmuti; Zuldadan Naspendra; Syaifuddin Islami (Jurusan Budidaya Perkebunan, 2022)
Indonesia is the third largest coffee exporting country in the world after Vietnam. In the current era of trade globalization, market competition is increasingly more stringent, where each country opens up their markets to one another. Therefore, we need to analyze the competitiveness and development of Indonesian coffee agribusiness. Competitiveness The analysis is perfomed by analyzing the comparative advantage Revealed Comparative Advantage (RCA) and competitive advantage with Diamond Porter's theoretical approach. The results show that Indonesian coffee, especially West Sumatra, has a competitive advantage, both comparative and competitive. The analysis used for produce an agribusiness development strategy is by SWOT analysis (Strengths, Weaknesses,Opportunities and Threats). The strategy resulting from the analysis is more focused on the technical aspect and cultivation of coffee commodity development.